Quantae psychologiae? – Una vel multae? - Todorović, Milorad V (Zbornik radova Filozofskog fakulteta u Prištini, 2016)
Concerned with the study of empirical correlations between elements of behavior and external circumstances, and especially with the research of these empirical relationships in a much simpler manner than it would be suitable for their complex nature, many psychologies rarely look at the fundamental issues of capability, or assumptions, of their own noetic efforts. Instead, there are multiple “views” that pretend to be psychological theories. The concept of psychology as a study of soul necessarily relies on the concept of science, and on the concept of soul as its subject. It is still the case – especially in academic circles – that the ruling concept of science is the modern, Cartesian, scientific concept where natural science is the only paradigm of science. When applied to the science of soul, that scientific paradigm inevitably gives different variations of reductionist psychology: from experimental psychology to neurophysiology. The truth (or factual knowledge as content) of such studies of soul must inevitably be reduced and scarce, namely, a reduced and scarce knowledge of soul itself. General psychological theory, of course, cannot be a compromise formation of disparate attitudes, rules and principles, nor can it, epistemologically, be an eclectic knowledge of mental phenomena. If different psychological theories, approaches, and points of view, which are sometimes, pretentiously, being called schools, see each mental theme or content in a totally different way, then it is necessary to examine the type, quality and place of the truth those psychologies strive for. It is not logical to expect such different approaches to reach the same truth, the same understanding of the correlations of psychological facts. In that case, the most logical question that can be asked is whether it is the same area of ​​research and whether it is the same science about psyche.